Sequential Treatment of Arterial Occlusions with Porcine Plasmin and Low Dose Streptokinase - Marbet, G A; Eichlisberger, R; Duckert, F; da Silva, M A; Biland, L; Widmer, L K; Ritz, R; Schmitt, H E (Thrombosis and Haemostasis, 1982)
Sequential treatment of arterial occlusions of the leg with porcine plasmin and low dose streptokinase results in a strong systemic proteolysis as already seen in deep leg vein thrombosis. In 31 of 45 patients the blood flow through major arterial segments could be restored. Thrombolytic success is possible within the first two treatment days but for the majority of the cases fibrinolytic therapy for 3-6 days is needed. On the average treatment was 1 day shorter than in DVT cases. No statistical relationship between local thrombolysis and systemic proteolysis was detected.The thrombolytic efficacy of this regimen compares favourably with earlier experience on fibrinolytic therapy in arterial occlusions.
Keywords: Arterial occlusion; Thrombolysis; Porcine plasmin; Streptokinase; Coagulation parameters; Fibrinolysis parameter; Thrombolysis duration